2019
DOI: 10.3390/ijms20205102
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Early Exposure of Isoflurane on Chronic Pain via the Mammalian Target of Rapamycin Signal Pathway

Abstract: Persistent post-surgical pain (PPSP) is a chronic pain condition, often with neuropathic features, that occurs in approximately 20% of children who undergo surgery. The biological basis of PPSP has not been elucidated. Anesthetic drugs can have lasting effects on the developing nervous system, although the clinical impact of this phenomenon is unknown. Here, we used a mouse model to test the hypothesis that early developmental exposure to isoflurane causes cellular and molecular alteration in the pain percepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…mTOR is a serine/threonine protein kinase that forms the catalytic subunit of two protein complexes, mTOR Complex 1 (mTORC1) and 2 (mTORC2) that regulate distinct cellular processes. Ribosomal protein S6, a downstream target of mTOR, is a component of Complex 1 and phosphorylated (p)S6 has been used as a specific marker of mTORC1 activation (Li, Mathena, Eregha, & Mintz, 2019; Yuskaitis et al., 2018). The mTORC1 cascade triggers mRNA translation and protein synthesis important for neuronal plasticity, while mTORC2 is associated with cell survival and proliferation (Hoeffer and Klann, 2010; Saxton & Sabatini, 2017; von Manteuffel et al., 1997).…”
Section: Introductionmentioning
confidence: 99%
“…mTOR is a serine/threonine protein kinase that forms the catalytic subunit of two protein complexes, mTOR Complex 1 (mTORC1) and 2 (mTORC2) that regulate distinct cellular processes. Ribosomal protein S6, a downstream target of mTOR, is a component of Complex 1 and phosphorylated (p)S6 has been used as a specific marker of mTORC1 activation (Li, Mathena, Eregha, & Mintz, 2019; Yuskaitis et al., 2018). The mTORC1 cascade triggers mRNA translation and protein synthesis important for neuronal plasticity, while mTORC2 is associated with cell survival and proliferation (Hoeffer and Klann, 2010; Saxton & Sabatini, 2017; von Manteuffel et al., 1997).…”
Section: Introductionmentioning
confidence: 99%
“…All mice, except naïve, underwent SNI-evoked chronic pain. We did not set “Iso only” group in this study because effect of isoflurane exposure on intact animals had been investigated in our previous study [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our previous work shows that, in intact newborn mice, isoflurane exposure causes cellular and molecular alteration in the developing pain perception circuitry via a pathologic upregulation of mTOR signaling pathway and enhances sensitivity to painful stimuli [ 29 ]. In this study, we sought to test the overall hypothesis that early postnatal GA exposure alters the development of pain circuitry through effects caused by increased signaling in the mTOR pathway such that mice more are rendered more susceptible to chronic neuropathic pain.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a recent study also reported that rapamycin treatment had a long-lasting effect on reducing the expression of p-mTOR and phospho-s6 even up to 18 days in a rodent model of isoflurane exposure. 47 Future studies are needed to investigate how long the pharmacologic effects of rapamycin can last after multiple consecutive days of injections.…”
Section: Discussionmentioning
confidence: 99%